Suppression of Excessive Histone Deacetylases Activity in Diabetic Hearts Attenuates Myocardial Ischemia/Reperfusion Injury via Mitochondria Apoptosis Pathway - Yang Wu; Yan Leng; Qingtao Meng; Rui Xue; Bo Zhao; Liying Zhan; Zhongyuan Xia (Journal of Diabetes Research)
Background. Histone deacetylases (HDACs) play a pivotal role in signaling modification and gene transcriptional regulation that are essential for cardiovascular pathophysiology. Diabetic hearts with higher HDACs activity were more vulnerable to myocardial ischemia/reperfusion (MI/R) injury compared with nondiabetic hearts. We are curious about whether suppression of excessive HDACs activity in diabetic heart protects against MI/R injury. Methods. Diabetic rats were subjected to 45 min of ischemia, followed by 3 h of reperfusion. H9C2 cardiomyocytes were exposed to high glucose for 24 h, followed by 4 h of hypoxia and 2 h of reoxygenation (H/R). Results. Both MI/R injury and diabetes mellitus elevated myocardium HDACs activity. MI/R induced apoptotic cell death was significantly decreased in diabetic rats treated with HDACs inhibitor trichostatin A (TSA). TSA administration markedly moderated dissipation of mitochondrial membrane potential, protected the integrity of mitochondrial permeability transition pore (mPTP), and decreased cell apoptosis. Notably, cotreatment with Akt inhibitor partly or absolutely inhibited the protective effect of TSA in vivo and in vitro. Furthermore, TSA administration activated Akt/Foxo3a pathway, leading to Foxo3a cytoplasm translocation and attenuation proapoptosis protein Bim expression. Conclusions. Both diabetes mellitus and MI/R injury increased cardiac HDACs activity. Suppression of HDACs activity triggered protective effects against MI/R and H/R injury under hyperglycemia conditions through Akt-modulated mitochondrial apoptotic pathways via Foxo3a/Bim.